EE= E3LC3: Engaging Experiences Enabling Learning Connections between Curriculum and Career: Making experiential learning clear by customizing an overarching understanding to the needs of both educators and external stakeholders. - Maxwell, Katia; Morrison, Lucy; Thiele, Levi (Experiential Learning and Teaching in Higher Education, 2024)
The current movement to institutionalize Experiential Education (EE) reflects and acts as a response to contemporary concerns about the perceived value of investing in education. The authors delineate the need to collaborate within a shared understanding of the possibilities, diversity, and operational practicalities of EE across different units and communities. This article presents a flexible working definition of EE that is intended to be malleable and applicable across universities. Subsequently, this article explores how this definition can serve as a guiding framework for the development and implementation of EE in specific areas, offering insights from three distinct scholar-practitioners. The article argues for shared overarching understanding of EE, accompanied with opportunities to adapt and delineate further by different interested parties and units. Finally, practical steps are suggested for colleagues seeking to establish a definition of EE at their institutions or respective organizations. Tangible strategies for adapting to individual contexts will be unique and must navigate particular campus and community contexts. Characteristics, competencies, high-impact practices, principles, and other elements can be useful as guidelines, but the umbrella definition of EE will enable various departments to implement tailored approaches to connect classroom learning with real-world experiences and careers.